EXPERIMENTAL EVALUATION OF THE AERODYNAMIC PERFORMANCE OF SMALL WIND TURBINES CONFECTIONED IN 3D PROTOTYPING - Garré S. O.; Paula, A. V.; Luz, J. L. R.; Vecina, T. D. J.; Petry, A. P. (Revista de Engenharia Térmica, 2016)
This paper presents the experimental evaluation of the aerodynamic performance of two small wind turbines models with five blades in the Aerodynamic Tunnel Professor Debi Pada Sadhu. The models were confectioned on a reduced scale using 3D prototyping, the first one was designed using the blade element method, assuming the power coefficient of Betz, named Optimal Blade Betz (OBB) and the second is modified from the first one, named Optimal Blade Betz Modified (OBBM). The velocity distribution in the cross section of the tunnel was determined with the aid of a Pitot tube before the evaluation of the equipment. With the known tunnel velocity profile, the static torque of the prototypes were determined with the use of a digital torquemeter coupled to the machine axis, which recorded the readings for the speed range of 1 m/s to 9.88 m/s. Also with the torquemeter, were evaluated the influence of the angular position of the blades in the measured torque. The blades were designed allowing vary their angular position in the hub, thus changing the angle of attack, and by consequence, the torque produced. A photo tachometer was employed to measure the rotation of the model in free spin. With the experimental data, the curves of static torque and angular velocity were determined as a function of incident speed. Through experimental determination of the incident velocity profile and the velocity profile in the aerodynamic wake of each turbine, the variation of the amount of momentum of the outflow was evaluated, and so the power extracted by the rotor in free rotation. This study aims to contribute to the design of a real small wind turbine, informing the aerodynamic characteristics of the equipment that can be constructed with this layout. The experimental results demonstrate good approximation for torque and power to the results obtained by evaluation by element of the blade method. The turbine constructed with Optimal Betz Blades presented static torque 17.8% higher than constructed with the Modified Blades and extracted 22% more power from the air outflow.